Role And Function of The Media on Dissemination of Information for Hiv/Aids Prevention at Radio and Television Timor-Leste in Díli Municipality - joaquim Pinto; Joaquim Gregorio de Carvalho; José Dionisio Ximenes; Abrão dos Santos Xavier; Natalia Pereira; Ermelinda da Costa Monteiro; Eugenia Carvalho de Araújo (International Journal of Multidisciplinary Research and Studies, 2026)
Background: HIV (Human Immunodeficiency Virus) is a type of virus that infects white blood cells (leukocytes) that causes a decrease in immunity in the human body. AIDS (Acquired Immunodeficiency Syndrome) is the accumulation of symptoms that occur due to the decrease of the body's immunity caused by HIV infection (Rosa, 2024). According to the World Health Organization (WHO, 2023) global HIV statistics report that there are 39.9 million people living with HIV, 1.3 million new HIV infections, 630,000 deaths from AIDSrelated diseases and 307 million people accessing antiviral therapy per year (Joint United Nations Program on HIV/AIDS (UNAIDS), 2024). According to the report of the National Institute to Combat HIV/AIDS (INCSIDA,2025), the total number of HIV/AIDS positive cases in Timor-Leste is 2,042, with the highest number of cases occurring in the municipality of Dili with 1,545, Bobonaro with 117, Covalima with 83, Oecusse with 63 and Baucau with 53 non-HIV/AIDS cases. to 50 are Ermera with 35 cases, Ainaro with 32, Likisa with 24, Manufahi with 22, Manatuto with 20, Lautem with 17, Aileu with 16 and Vikeke with 15 (INCSIDA, 2025). Objective: The objective of this study was find out the role and function of the media on the dissemination of information for HIV/AIDS prevention in Radio and Television of TimorLeste,Dili Municipality. Methods: In this research, the researcher used a quantitative correlational method with a crosssectional study approach. The sampling technique in this research is non probability sampling technique with Total Sampling type. Total population 65, sample 65. Sampling technique uses non probability sampling with type Total Sampling. The data analysis technique used ordinal spearman rho. Results: The results demonstrated that there was a significant relationship between media role and HIV/AIDS prevention with its correlation coefficient (0.570) and sig. (pvalue=0.000<0.05). And there was a significant relationship between the average function and HIV/AIDS prevention with its correlation coefficient (0.451) and sig. (pvalue=0.000<0.05). Conclusion: function of media are significantly relationship with HIV/AIDS prevention. Emphasizing the importance for the media to carry out its roles and functions correctly and effectively. Doi:-10.5281/zenodo.19106587